Semi-quantitative Digital Analysis for Human Papillomavirus Detection from Environmental Specimens - Adelina Siagian; Dicky Bagus Pratama; Fahmy Fathurrohman; Lia Faridah; Savira Ekawardhani (Faculty of Medicine Universitas Padjadjaran, 2020)
Background: Recently, human papillomavirus (HPV) deoxyribonucleic acid (DNA) has been detected in urban wastewater, indicating that the virus can reach the sewer and, eventually, other water environments. This study aimed to develop a semi-quantitative assay for HPV DNA detection from environmental specimens using the PCR gel electrophoresis method.Method: This was an experimental descriptive qualitative study conducted from July to November 2019 in a standard molecular laboratory and non-laboratory administration room without air conditioner. Three brands of PCR reagents and different annealing temperatures were compared to identify the best condition for conventional PCR of plasmid DNA containing the HPV L1 gene. The semi-quantitative data were obtained from densitometry digital analysis using an imaging software. The optimized protocol was then applied on DNA serial dilutions to seek for the lower limit of detection (LLOD) value and the linear range of the assay. To evaluate the robustness of the assay, the protocol was further applied to spiked specimens of wastewater. Finally, several wastewater samples were tested for the presence of HPV DNA using this protocol.Results: A broad linear range and HPV L1 gene detection ability were observed with an LLOD of less than 2pg plasmid DNA in field condition. Although the assay successfully detected HPV DNA from several spiked wastewater samples, certain wastewater could interfere with the assay and gave false negative result.Conclusion: A semi-quantitative conventional PCR method to detect HPVDNA from environmental samples has been established and proven to be robust in field condition with non-optimum cold chain.